Insight of vitellogenesis patterns: A comparative analysis of the differences between the primary and secondary vitellogenesis period in the ovary, hepatopancreas, and muscle of mud crab, scylla paramamosain - Ren, Yuanhao; Wang, Wei; Liu, Zhiqiang; Luo, Minghao; Fu, Yin; Zhang, Fengying; Ma, Chunyan; Zhao, Ming; Chen, Wei; Jiang, Keji; Ma, Lingbo (Frontiers in Genetics, 2022)
The mud crab, Scylla paramamosain, has abundant nutrients in its edible parts, ovary, hepatopancreas, and muscle during the ovarian maturation stage. The ovary of S. paramamosain can re-mature after spawning during the secondary ovarian maturation period. We aimed to analyze the characteristics of the first vitellogenesis period (FVP) and second vitellogenesis period (SVP) of S. paramamosain during ovarian maturation to understand the differences in vitellogenesis patterns between the first and second ovarian maturation periods. Accordingly, the gonadosomatic index (GSI) and hepatopancreatic index (HSI), the external and histological characteristics of the ovary and hepatopancreas, the Sp-Vg (vitellogenesis, Vg) expression levels in the hepatopancreas and ovary, and the dynamics of the biochemical components in the ovary, hepatopancreas, and muscle were determined. Based on the results, the GSI was significantly positively correlated with HSI during the FVP and significantly negatively correlated with HSI from stage Ⅳ to stage Ⅴ of the SVP. A significant difference was found between the FVP and SVP in the hepatopancreas. Notably, the hepatopancreas displayed a gradual degeneration trend during the SVP. The expression level of Sp-Vg was significantly higher in the hepatopancreas than that in the ovary during the FVP and SVP. Seventeen amino acids were detected in the hepatopancreas, ovary, and muscle during the FVP and SVP, with glutamate as the predominant amino acid. During the FVP and SVP, the C16:0 and C18:1n9c were the dominant fatty acids in the hepatopancreas and ovary, the MUFA gradually increased in the ovary and hepatopancreas, and a significant difference was found in the dynamic trend of the HUFA and SFA contents from stage Ⅳ to stage Ⅴ between the FVP and SVP. These findings indicate that the ovary can re-mature after spawning in S. paramamosain and can maintain the status of the first ovarian maturation; however, the hepatopancreas gradually degenerate during the SVP.